Estimation of Junction Temperature in a Two-Level Insulated-Gate Bipolar Transistor Inverter for Motor Drives - Kim, Seong Yun; Jo, Ha Rang; Cho, Sungjoon; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2022)
This paper presents a method for junction temperature estimation using the mathematical thermal model in a two-level insulated-gate bipolar transistor (IGBT) inverter for motor drives. A power conversion system (PCS) comprises various components, and IGBT switches are the key components determining the reliability of the PCS. One of the challenges with regard to a PCS is improving its reliability. The failure of IGBTs is mainly due to variations in the junction temperature. To predict the lifetime of the PCS, the thermal behavior of the IGBT must be defined. The thermal behavior is dependent on the current that flows to the IGBT, and the load current profile is specific to the application. Generally, the switch module is encapsulated; therefore, an additional manufacturing process is necessary for measuring the junction temperature. The presented temperature estimation method using a mathematical model does not require an additional process for temperature measurement. An experiment is conducted using a diode-doped FS150R12KT4 module to determine the thermal profile of the IGBT for 11-kW interior permanent magnet synchronous motor drives. The effectiveness of the presented estimation method is verified by the simulation and experimental results.
Keywords: Insulatedgate bipolar transistor (IGBTs); Junction temperature estimation; Junction temperatures; Motor drive; Power conversion systems; Powerloss; Reliability of power conversion system; Temperature estimation; Thermal behaviours; Two-level inverters; Insulated-gate bipolar transistor; Junction temperature estimation; Motor drives; Power losses; Reliability of power conversion system; Thermal stress; Two-level inverter